Dietary supplementation with yerba mate (Ilex paraguariensis) infusion increases IRS-1 and PI3K mRNA levels and enhances insulin sensitivity and secretion in rat pancreatic islets - Maiztegui, Bárbara (2023)
“Yerba mate” (YM), an aqueous extract of Ilex paraguariensis, has antioxidant, diuretic, cardio-protective and hypoglycaemic properties. Since its effect on the pancreatic islets remains unclear, we evaluated insulin sensitivity and glucose-stimulated insulin secretion (GSIS) in rats consuming YM or tap water (C) for 21 days. Glucose tolerance, glycemia, triglyceridemia, insulinemia, TBARS and FRAP serum levels were evaluated. GSIS and mRNA levels of insulin signaling pathway and inflammatory markers were measured in isolated pancreatic islets from both groups. In C rats, islets were incubated with YM extract or its phenolic components to measure GSIS. YM improved glucose tolerance, enhanced GSIS, increased FRAP plasma levels and islet mRNA levels of IRS-1 and PI3K (p110), and decreased TBARS plasma levels and islet gene expression of TNF-α and PAI-1. Islets from C rats incubated with 100 µg/mL dry YM extract, 1 µM chlorogenic acid, 0.1 and 1 µM rutin, 1 µM caffeic acid or 1 µM quercetin showed an increase in GSIS. Our results suggest that YM enhances glucose tolerance because of its positive effects on GSIS, oxidative stress rate and insulin sensitivity in rat islets, suggesting that long-term dietary supplementation with YM may improve glucose homeostasis in pre-diabetes or type 2 diabetes.